2019
DOI: 10.1371/journal.pone.0217120
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of long-term outcomes between enteral nutrition via gastrostomy and total parenteral nutrition in older persons with dysphagia: A propensity-matched cohort study

Abstract: BackgroundThe long-term outcomes of artificial nutrition in older people with dysphagia remain uncertain. Enteral nutrition via percutaneous endoscopic gastrostomy (PEG) is one of the major methods of artificial nutrition. Enteral feeding is indicated for patients with a functional gastrointestinal tract. However, total parenteral nutrition (TPN) is often inappropriately chosen for artificial nutrition in Japan, even in patients with a functional gastrointestinal tract, as PEG has recently been viewed as an un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Because of the nature of the claims this study focused on the survival intervals between the initiation of enteral feeding and PN during hospital admission and death in all the settings, regardless of whether their uses were continued. Considering that previous studies on prognoses of NGT or PN evaluated the periods between initiation and death [ 16 , 35 ], our findings are comparable with those of these studies. However, to address these concerns, further research is needed to clarify the prognoses associated with enteral feeding and PN in patients with different conditions and circumstances.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Because of the nature of the claims this study focused on the survival intervals between the initiation of enteral feeding and PN during hospital admission and death in all the settings, regardless of whether their uses were continued. Considering that previous studies on prognoses of NGT or PN evaluated the periods between initiation and death [ 16 , 35 ], our findings are comparable with those of these studies. However, to address these concerns, further research is needed to clarify the prognoses associated with enteral feeding and PN in patients with different conditions and circumstances.…”
Section: Discussionsupporting
confidence: 91%
“…They found that the survival period was significantly longer in the PEG group (median, 317 days) than that in the PN group (195 days). Although the study excluded patients with advanced cancer [ 35 ], our study demonstrated better prognoses within 2 years for enteral nutrition than for PN in patients with and without malignant diseases. Moreover, long-term PN places patients at risk for catheter-related blood-stream infections and bacterial translocation [ 35 37 ].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Enteral feeding is indicated for patients with a functional gastrointestinal tract, whereas parenteral feeding is more commonly used for patients with nonfunctional gastrointestinal tract [ 10 ]. In general, enteral nutrition is preferred to parenteral nutrition as it is more physiological, simpler, cheaper, and less complicated [ 11 ].…”
Section: Malnutritionmentioning
confidence: 99%